Digitalisation assistance of semprong and simping Small and Medium Enterprises (SME) in Desa Taringgul Tonggoh Wanayasa - Adinda Nur Hanifa; Aletha Irshaina Rasheefah; Isnaeni Fajar Fatkhurahmah (Universitas Pendidikan Indonesia, 2023)
Digitalisation is one of the steps in managing Small and Medium enterprises (SMEs) that now needs to be taken as technology develops. Business digitalisation by SMEs in Indonesia is still not implemented and paid enough attention, including by Taringgul Tonggoh Village, Wanayasa District, Purwakarta Regency. This results in several problems for SMEs founders, such as obstruction of product promotion and marketing activities, which can affect the development of SMEs themselves. So, digitalisation assistance is needed for SMEs so they can maximize digitalisation. This service was carried out in Taringgul Tonggoh Village to provide SMEs players with an understanding of the use of digital media in running SMEs. The methods used in this program are socialization, mentoring, and surveys. The results obtained from this program are an increased understanding of online product marketing and social media management for SMEs. This program also updates logos and labels and registers production house locations on Google Maps. Business digitalization can provide great opportunities for SMEs to increase buyer interest. Abstrak Digitalisasi menjadi salah satu langkah dalam pengelolaan UMKM yang kini perlu dilakukan seiring berkembangnya teknologi. Digitalisasi usaha oleh UMKM di Indonesia masih kurang diterapkan dan diperhatikan, termasuk oleh Desa Taringgul Tonggoh, Kecamatan Wanayasa, Kabupaten Purwakarta. Hal tersebut mengakibatkan beberapa permasalahan bagi para pendiri UMKM seperti seperti terhambatnya kegiatan promosi dan pemasaran produk yang dapat berpengaruh pada perkembangan UMKM itu sendiri. Sehingga dibutuhkan suatu pendampingan digitalisasi bagi para UMKM agar dapat memaksimalkan digitalisasi. Pengabdian ini dilaksanakan di Desa Taringgul Tonggoh, guna memberiksn pemahaman kepada pelaku UMKM mengenai penggunaan media digital dalam menjalankan UMKM. Metode yang digunakan dalam program ini adalah sosialisasi dan pendampingan serta survei. Hasil yang diperoleh dari program ini ialah bertambahnya pemahaman mengenai pemasaran produk secara daring serta pengelolaan media sosial untuk UMKM. Selain itu, pada program ini dilakukan pula pembaruan logo dan label serta pendaftaran lokasi rumah produksi di Google Maps. Digitalisasi bisnis dapat memberikan peluang besar bagi UMKM untuk meningkatkan minat pembelinya. Kata Kunci: Digitalisasi usaha; kuliah kerja nyata; UMKM